Diagnosis, treatment and outcome of spinal lymphoma in a pony. (30th September 2013) - Finding, E. J. T.; Ciasca, T.; Pinilla, M. J.; Driver, C. J.; Johns, I. C.; Weller, R.; Volk, H. A.
Summary This report describes the diagnostic approach to, and treatment of, a case of severe pelvic limb ataxia in a Miniature Shetland pony. Diagnosis of an intradural‐extramedullary lesion at the level of T11–12 was made using CT myelography. Dorsolateral hemilaminectomy allowed surgical debulking of an intradural mass, diagnosed histopathologically as T cell rich B cell lymphoma. Post operative treatment with prednisolone, cytarabine and cyclophosphamide was tolerated well and the degree of ataxia reduced markedly, allowing the pony to return to normal management.